2012
DOI: 10.1038/ng.2231
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis identifies nine new loci associated with rheumatoid arthritis in the Japanese population

Abstract: Rheumatoid arthritis is a common autoimmune disease characterized by chronic inflammation. We report a meta-analysis of genome-wide association studies (GWAS) in a Japanese population including 4,074 individuals with rheumatoid arthritis (cases) and 16,891 controls, followed by a replication in 5,277 rheumatoid arthritis cases and 21,684 controls. Our study identified nine loci newly associated with rheumatoid arthritis at a threshold of P < 5.0 × 10(-8), including B3GNT2, ANXA3, CSF2, CD83, NFKBIE, ARID5B, PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
249
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(269 citation statements)
references
References 27 publications
8
249
0
1
Order By: Relevance
“…Recent studies showed two autoimmune diseases, sclerosis and rheumatoid arthritis, were related to PLD4 mutation (16,17). Although PLD4 seemed to have some immunological functions, little was known about its function in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed two autoimmune diseases, sclerosis and rheumatoid arthritis, were related to PLD4 mutation (16,17). Although PLD4 seemed to have some immunological functions, little was known about its function in cells.…”
Section: Discussionmentioning
confidence: 99%
“…After treated with LPS, the expression of the PLD4 in microglia was increased which could promote the function of phagocytosis (15). Recent studies have indicated mutation in PLD4 gene was associated with two autoimmune diseases, named systemic sclerosis (16) and rheumatoid arthritis (17), both had abnormal inflammatory skin lesions symptoms (18). Although PLD4 was involved in microglia phagocytosis, there is little known on its function and the mechanism, thus PLD4 needed to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have identified loci associated with increased susceptibility to renal dysfunction in humans (12,13). Additionally, mouse models and genome-wide transcriptome analyses of kidneys from patients with CKD and fibrosis have facilitated the identification of a number of signaling pathways associated with renal fibrosis, including the Notch, Wnt, and Hedgehog pathways (3).…”
mentioning
confidence: 99%
“…Several genome-wide association studies revealed numerous gene loci that mediate susceptibility to IBD [4]. Among them is the locus encoding the protein tyrosine phosphatase non-receptor type 2 (PTPN2) (also called T cell protein tyrosine phosphatase (TCPTP)) [5,6], which was also found to be associated with other chronic inflammatory and autoimmune diseases such as type 1 diabetes (T1D) and rheumatoid arthritis (RA) [7,8]. …”
Section: Introductionmentioning
confidence: 99%